Seasonal maize forecasting for South Africa and Zimbabwe derived from an agroclimatological model - Martin, R; Washington, R; Downing, T (Americal Meteorological Society, 2000)
Seasonal maize water-stress forecasts were derived for area averages of the primary maize-growing regions of South Africa and Zimbabwe. An agroclimatological model was used to create a historical record of maize water stress as a function of evapotranspiration for 1961-94. Water stress, the primary determinant of yield in water-limited environments such as southern Africa, was correlated with two well-known indices of the El Niño - Southern Oscillation: the Southern Oscillation index (SOI) and the Niño-3 region of the equatorial Pacific. Forecasts for South Africa using only the SOI at a 4-month lead yielded a hindcast correlation of 0.67 over 17 seasons (1961-78) and a forecast correlation of 0.69 over 16 seasons (1978-94). Forecasts for Zimbabwe were less remarkable.